Meningkatkan Kemampuan Memakai Baju Berkancing Melalui Teknik Total Task Presentation Pada Anak Sindrom Down - Asih Qurratunayun; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2022)
Preliminary study in class IV SLB was found a child the initials M had problems wearing button-down clothes. The provision of appropriate learning techniques is needed. Total task presentation was chosen as a way to improve the ability to wear button-down clothes for children with Down syndrome. Study used Single Subject Research (SSR) with an A-B-A design and using graphic visual analysis techniques. The subject was 13 y.o with down syndrome, grade IV at SLB Ummi Khaira, West Pasaman Regency. The data collection technique used an action test instrument. The results showed an increase in the ability to wear button-up shirts in the analysis data under conditions and analysis between conditions. The mean level of condition A1 (15,78) is lower than condition B (69,73) and A2 (94,74). The results of this study show that total task presentation can improve the ability to wear button-down shirts for children with Down syndrome.